The Effects of Adolescent Self-Regulated Learning on Engagement in a College Access Program: An Exploratory Study - James M. Ellis; Lumas J. Helaire (SAGE Publishing, 2018)
College access programs (CAPs) aim to promote college readiness for adolescents, particularly those who may be the first in their family to go to college. Self-regulated learning is a critical component of college readiness. There is limited information about how self-regulated learning beliefs or intentions influence adolescent engagement in CAPs. Using the theory of planned behavior as a guiding framework, the purpose of this study was to examine direct and indirect effects of adolescent self-regulated learning beliefs (i.e., attitudes, norms, and perceived behavioral control) and intentions on participation in activities offered by a regional, federally funded CAP program (Gaining Early Awareness and Readiness for Undergraduate Programs; GEAR UP). Structural equation modeling was the analytic technique. We found positive relationships between self-regulated learning beliefs (perceived behavioral control), intentions, and GEAR UP participation. Implications and directions for future research on self-regulated learning within the context of CAP initiatives are discussed.